Modified Unequally Spaced Channels Wavelength Division Multiplexing System - Hassan Yasser (مجلة علوم ذي قار, 2019)
The channels contributed in creating new pulse during the four-wave mixing (FWM) process are a subject of two features: the first is the fact that all channels are not working with probability